2021
DOI: 10.26822/iejee.2021.200
|View full text |Cite
|
Sign up to set email alerts
|

How primary teachers use games to support their teaching of mathematics

Abstract: Mathematical games are widely employed by Australian primary school teachers to support mathematics instruction. Despite broad usage, prior research has not focused on the how and why games are employed from a teacher perspective. Australian primary school teachers (n = 248) completed a questionnaire designed to probe their experience with mathematical games in the classroom, specifically; motivation for and frequency of game usage, game execution within lesson routines and structures, and, perceptions of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 25 publications
0
4
0
1
Order By: Relevance
“…It is essential to understand whether what academics and researchers publish about games and EGs aligns with game designers' perspectives. As games provide endless positive possibilities (Russo, 2021), it is critical to adhere to game designers' aspects as the first-end users who play-test the game/EGs. The validity consideration of data analysis towards the authenticity and accuracy throughout the research is achieved through techniques including triangulation (examining with theoretical concepts, investigator, and data triangulation), and peer debriefing, prolonged and persistent engagement with the raw data set to allow critical and clarity throughout the analysis and emergence of themes to be compared.…”
Section: Thematic Analysis and Interpretive Results Discussionmentioning
confidence: 99%
“…It is essential to understand whether what academics and researchers publish about games and EGs aligns with game designers' perspectives. As games provide endless positive possibilities (Russo, 2021), it is critical to adhere to game designers' aspects as the first-end users who play-test the game/EGs. The validity consideration of data analysis towards the authenticity and accuracy throughout the research is achieved through techniques including triangulation (examining with theoretical concepts, investigator, and data triangulation), and peer debriefing, prolonged and persistent engagement with the raw data set to allow critical and clarity throughout the analysis and emergence of themes to be compared.…”
Section: Thematic Analysis and Interpretive Results Discussionmentioning
confidence: 99%
“…Regarding the last sub-problem of the research, the results obtained from the studies show that in 65% of the studies, mathematics teaching with games had a positive effect. Research has shown that teaching with games increases students' academic achievement (Divjak & Tomić, 2011;Karamert, 2019;Pehlivan, 2020;Türkmen, 2017) and positively affects their attitudes toward mathematics ( Tükle, 2020), and that research participants have a positive attitude toward the use of games in mathematics courses (Koç-Deniz, 2019;Russo et al, 2021;Watson-Huggins, 2018).These results are in line with previous research studies conducted on this subject (Divjak & Tomic, 2011;Turgut & Temur, 2017;Türker & Arslan, 2021). However, in studies where negative effects were observed, it was found that teachers were not aware of the use of games in mathematics teaching (Pilten, Pilten, Divrik & Divrik, 2017) and that there was a lack of harmony between technological games and pedagogical principles ( Lindström, Gulz, Haake & Sjödén, 2011).In addition, results are also included on teachers' need for game materials (Kondratieva & Freiman, 2011), the low use of games in some countries (Nabie, 2008), some needs for integrating game use into the curriculum (Akintunde et al, 2020;Callaghan, Long, van Es, Reich, & Rutherford, 2017;Fouze & Amit, 2018;Graceota & Slamet., 2021;Koneva & Shabanova, 2021;Shabrina et al, 2020), the effects of designing game components and the effects of game design (Ke, 2014;Rawansyah et al, 2021;Trujillo, Chamberlin, Wiburg & Armstrong, 2016), and the inappropriateness of using games according to certain standards (NCTM) (Joung & Byun, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…When examining the studies that use the method of teaching with games, it was found that teaching with games increases academic achievement (Liang, Zhang, Long, Deng & Liu, 2019;Rawansyah, Pramudhita & Pramitarini, 2021;Rondina & Roble, 2019) and positively affects attitudes toward mathemati cs instruction (Chiang & Qin, 2018;Tuekle, 2020), and that research participants positively evaluate the use of games in mathematics instruction (Bragg, 2007;Koç-Deniz, 2019;Russo, Bragg & Russo, 2021;Watson-Huggins, 2018).Along with the increase in studies conducted on teaching mathematics with games in recent years, compilation studies are also encountered (Divjak & Tomić, 2011;Joung & Byun, 2020;Türker & Arslan, 2021). Divjak and Tomić (2011) analyzed 32 studies conducted between 1995 and 2010, in which an attempt was made to determine the effect of games on motivation and achievement of learning goals in mathematics education through the use of mathematical computer games.…”
Section: Introductionmentioning
confidence: 99%
“…In practice, primary school teachers tend to use non-digital mathematical games to support maths learning (board, dice, and card games). According to Russo and Russo (2020) and Russo et al (2021) almost all the primary teachers admitted playing mathematical games in their classrooms a minimum of once a week, they view games as highly effective for developing all four proficiencies highlighted in the Mathematics Curriculum: fluency, understanding, problem-solving, and reasoning. According to Dienes (2015), activities, games and concrete experiences should be the base of learning mathematics, that could be a joyful experience with the use of tools that enhance efficiency.…”
Section: Introductionmentioning
confidence: 99%